The early management of meningococcal disease. Issue 2 (March 1998) - Hodgetts, T J; Brett, A; Castle, N
Abstract : Meningococcal disease is a fulminant infection with an overall mortality of 8%. Mortality is significantly increased with meningococcal septicaemia, particularly when there has been a delay in the diagnosis. The trend from 1985 to 1995 has been an increase in incidence of this disease, and the relative importance of meningococcal disease has also increased following a fall in the incidence of invasive Haemophilus influenzae disease with childhood immunisation. The management of such cases can be complex and time critical. Patients with meningococcal septicaemia often require aggressive resuscitation, including airway support, intravenous colloid, and parenteral antibiotics; hypoglycaemia is also commonly seen, and inotropes may be needed to support the circulation. We examine the treatment strategies in the early management of meningococcal disease and provide an algorithm for use by ambulance personnel, general practitioners, accident and emergency clinicians, and paediatricians. The objective of this algorithm is to ensure that an optimally resuscitated patient is delivered to the definitive care facility.